2008
DOI: 10.1210/jc.2007-1989
|View full text |Cite
|
Sign up to set email alerts
|

Paraganglioma after Maternal Transmission of a Succinate Dehydrogenase Gene Mutation

Abstract: Our data show that maternal transmission of a SDHD-linked PGL, even if a rare event, can occur. Therefore, we propose that children who inherited a pathogenic mutation from their mother should be considered as at risk of PGL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 19 publications
2
45
0
1
Order By: Relevance
“…22 Within this model, paraganglioma formation occurs only when the wild-type maternal SDHD allele on 11q23 and the active copy of the imprinted TSG on 11p15 are simultaneously lost. This model of inheritance has been supported by the report of Pigny et al, 24 who describe the only known case of maternal transmission of SDHDlinked paraganglioma to date. Although at first sight, this unique case seems to contradict the model, it was shown that the patient had also acquired an altered methylation profile and, therefore, probably an altered imprinted status of H19, a known paternally imprinted TSG on 11p15.…”
Section: Penetrancementioning
confidence: 59%
See 1 more Smart Citation
“…22 Within this model, paraganglioma formation occurs only when the wild-type maternal SDHD allele on 11q23 and the active copy of the imprinted TSG on 11p15 are simultaneously lost. This model of inheritance has been supported by the report of Pigny et al, 24 who describe the only known case of maternal transmission of SDHDlinked paraganglioma to date. Although at first sight, this unique case seems to contradict the model, it was shown that the patient had also acquired an altered methylation profile and, therefore, probably an altered imprinted status of H19, a known paternally imprinted TSG on 11p15.…”
Section: Penetrancementioning
confidence: 59%
“…Although at first sight, this unique case seems to contradict the model, it was shown that the patient had also acquired an altered methylation profile and, therefore, probably an altered imprinted status of H19, a known paternally imprinted TSG on 11p15. 24 This suggests that the parent-of-origin-dependent inheritance of SDHD-linked disease is caused by the paternal imprinting of H19, a TSG on the imprinted 11p15 region that seems to be essential for paraganglioma formation. It furthermore suggests that maternal transmission of SDHD-linked disease is possible only if the 'second hit' targets the wild-type paternal SDHD allele on 11q23 as well as the active status of the maternal H19 allele on 11p15.…”
Section: Penetrancementioning
confidence: 99%
“…Multifocal tumours are more common with SDHD mutations (22). It should be noted that the tumour risk with SDHD mutations is for mutations that have been paternally inherited (maternally transmitted mutations have only very rarely been linked with disease and routine surveillance is not indicated in such cases) (24,25). Mean age at diagnosis of phaeochromocytoma in patients with SDHD mutations is 35 years (23).…”
Section: The Succinate Dehydrogenase Complexmentioning
confidence: 99%
“…SDHB mutations are an important cause of HNPGL and aPCA/eFPGL (13,23,24,26). In addition, SDHB mutations predispose to renal tumours and may present with familial renal cell carcinoma (RCC) (27).…”
Section: The Succinate Dehydrogenase Complexmentioning
confidence: 99%
“…For PGL 1, maternal imprinting of the susceptibility gene has been proposed, thus implying that only a carrier inheriting the mutation from the father will develop the disease; an exception to this rule has been observed, but the case is unclear. 22,23 The presence of several reports of familial non-syndromic cases indicates that the prevalance of inherited cases might be higher than currently recorded. 24,25 A summary of pheochromocytoma presentation in the different syndromes is represented in Table 1.…”
mentioning
confidence: 99%